Prinsip Teologi Multikultural sebagai Fondasi bagi Kehidupan Menggereja Di Tengah Keragaman - Franky Franky (Sekolah Tinggi Teologi Kalimantan, 2023)
Speaking of the church as a common life (communion-koinonia), the church cannot be separated from the reality of diversity (multiculturality). Multiculturality in the church community, in addition to enriching the life of Service and fellowship, not least also resulted in ‘friction’ among the congregation. The church, which is supposed to bring brotherly harmony to all of God's children, is instead contaminated with various conflicts of interest. Based on the existing problems, it takes the right strategy to deal with all forms of problems that occur in diverse church communities to produce a solid community that uses the principles of multicultural theology. To achieve the research objectives that have been described above, the method used a descriptive qualitative approach through literature study. The primary and secondary data collection techniques, use library study techniques. Through the method used, the results found that the principles of multicultural theology such as: first, the nature of man as creation is the basis of multiculturality; second, the incarnation of Christ as the Christological basis for relations between multicultural congregations and third, the naturality aspect of the church in interacting in a multicultural congregation is very important to understand and further implement in church life amid diversity so as to produce a solid community in the church.Berbicara mengenai gereja sebagai kehidupan bersama (persekutuan-koinonia), maka gereja tidak lepas dari realitas keragaman (multikulturalitas). Multikulturalitas dalam komunitas gereja, selain memperkaya dalam kehidupan pelayanan dan persekutuan, tidak sedikit juga mengakibatkan ‘gesekan’ di antara jemaat. Gereja yang seharusnya menghadirkan kerukunan bersaudara dengan semua anak Allah, malah terkontaminasi dengan beragam konflik kepentingan. Berdasarkan permasalahan yang ada, dibutuhkan strategi yang tepat dalam menyiasati segala bentuk problematika yang terjadi dalam komunitas gereja yang beragam sehingga menghasilkan komunitas yang solid yakni menggunakan prinsip-prinsip teologi multikultural. Untuk mencapai tujuan penelitian yang telah dipaparkan diatas, maka metode yang digunakan dengan pendekatan kualitatif deskriptif. Adapun teknik pengumpulan data, baik primer maupun sekunder melalui studi kepustakaan. Melalui metode yang digunakan, maka hasil yang ditemukan bahwa prinsip-prinsip teologi multikultural seperti: pertama, natur manusia sebagai ciptaan menjadi dasar multikulturalitas; kedua, inkarnasi Kristus sebagai dasar Kristologis bagi relasi antar jemaat yang multikultur dan ketiga, aspek naturalitas gereja dalam berinteraksi di tengah jemaat yang multikultur sangat penting untuk dipahami dan selanjutnya diimplementasikan dalam kehidupan menggereja di tengah keragaman sehingga menghasilkan komunitas yang solid dalam gereja.